Analisis Kinerja Ruas Jalan Sudanco Supriyadi Kota Blitar - Peka , Lukas Ledu; Arifianto , Andy Kristafi; Rahma , Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Supriyadi Road is a pleasant urban road in Blitar City. It functions as a two-way two-lane collector road (2/2 UD) and is located in the PETA Monument area. The route has a length of 2.46 kilometers. This road section deserves close attention because it is surrounded by tourist attractions and schools. Parking activities at these locations occupy most of the road, resulting in a reduction in the effective width of the road. Around the PETA monument, which is about 200 meters long, there are four school areas: SMKN 3 Blitar, SMPN 3 Blitar, SMPN 5 Blitar, and SMPN 6 Blitar. In addition, there is the Bung Karno Tomb Tour. As a result, there tends to be a large density of people during peak hours in this area. This study aims to determine the performance of S.Supriyadi road in Blitar city and ensure predictions for the next five years. This research uses descriptive methodology and refers to the Indonesian Road Capacity Guidelines (PKJI, 2014). The results showed that the Degree of Saturation (DJ) value was recorded at 0.55 during the Monday peak hour, falling into the level of service C category. Meanwhile, the forecast for the next five years (2026) for DJ stands at 0.55. This indicates that the S. Supriyadi road section falls into the level of service C category, i.e. traffic flow remains stable but vehicle speed is regulated.